Investigation of Environmental Pollutant-Induced Lung Inflammation and Injury in a 3D Coculture-Based Microfluidic Pulmonary Alveolus System - Zhang, Fen; Liu, Wenming; Zhou, Sisi; Jiang, Ling; Wang, Kan; Wei, Yuanqing; Liu, Anran; Wei, Wei; Liu, Songqin (Analytical chemistry (Washington), 2020)
The health impact of environmental pollution involving an increase in human diseases has been subject to extensive study in recent decades. The methodology in biomimetic investigation of these pathophysiologic events is still in progress to uncover the gaps in knowledge associated with pollution and its influences on health. Herein, we describe a comprehensive evaluation of environmental pollutant-caused lung inflammation and injury using a microfluidic pulmonary alveolus platform with alveolar-capillary interfaces. We performed a microfluidic three-dimensional coculture with physiological microenvironment simulation at microscale control and demonstrated a reliable reconstruction of tissue layers including alveolar epithelium and microvascular endothelium with typical mechanical, structural, and junctional integrity, as well as viability. On-chip detection and analysis of pulmonary alveolus responses focusing on various inflammatory and injurious dynamics to the respective pollutant stimulations were achieved in the coculture-based microfluidic pulmonary alveolus model, in comparison with common on-chip monoculture and off-chip culture tools. We confirmed the synergistic effects of the epithelial and endothelial interfaces on the stimuli resistance and verified the importance of creating complex tissue microenvironments in vitro to explore pollution-involved human pathology. We believe the microfluidic approach presents great promise in environmental monitoring, drug discovery, and tissue engineering.